Memahami inti dari proses pengembangan kurikulum: Analisis kebutuhan, perancangan, dan formulasi - Abdul Karim Suhadha; Cepi Riyana; Ahmad Fajar Fadlillah; Eva Puspitasari; Amir Hamzah (Universitas Pendidikan Indonesia, 2026)
The rapid evolution of digital technology and artificial intelligence has rendered traditional curricula obsolete, necessitating an adaptive systemic reconstruction. This study aims to dissect the fundamental phases of curriculum development through the triad of needs analysis, design, and formulation within the framework of digital humanism. A Systematic Literature Review (SLR) method was applied to 22 primary scientific articles sourced from the Scopus database (2019-2025), in strict adherence to PRISMA guidelines. Findings indicate that the effectiveness of curriculum development is determined by methodological rigor and the balance between systems engineering and universal human values. Responsive needs analysis based on real-time data, resilient backward-design strategies, and formulation processes that account for socio-technical dynamics are identified as absolute prerequisites for curriculum relevance. The study concludes that technology must be positioned as a support for human agency through a development model that integrates Total Quality Management (TQM) with principles of digital humanism. Practical implications underscore the critical need to strengthen teachers' capacity and autonomy as primary actors in curriculum formulation. This research provides a theoretical foundation for developing adaptive curriculum models that empower learners amid massive technological disruption.